Nanotheranostics: Dual‐Stimuli Responsive Nanotheranostics for Multimodal Imaging Guided Trimodal Synergistic Therapy (Small 6/2017). Issue 6 (February 2017) - Fang, Shan; Lin, Jing; Li, Chunxiao; Huang, Peng; Hou, Wenxiu; Zhang, Chunlei; Liu, Jingjing; Huang, Sisi; Luo, Yongxiang; Fan, Wenpei; Cui, Daxiang; Xu, Yunsheng; et al.
Abstract : In article number 1602580, J. Lin, P. Huang, Y. Xu, Z. Li, and co‐workers present a light/pH dual‐stimuli responsive nanotheranostic for multimodal imaging such as two‐photon luminescence, fluorescence, photoacoustic, photothermal imaging, as well as trimodal synergistic therapy such as photothermal therapy, photodynamic therapy, and chemotherapy. The cover image depicts how this activatable theranostic nanoplatform fights against cancer like "ten thousand arrows shot at once".